Assessment Of The Level Of Creative Leadership Among Administrative Leaders In The Directorates Of Youth And Sports In The Central And Southern Regions - Saadoun Qasim Lazim (Wahid Hasyim University, 2026)
The importance of this research lies in evaluating the level of creative leadership among the administrative leaders of the youth and sports directorates in the central and southern regions. The research problem was that creative leadership is the optimal way to confront these challenges. A humanitarian necessity and a historical imperative for any institution, this is the cornerstone for developing and implementing strategies through which goals can be achieved. It is essential to ensure the suitability of the chosen strategy, and this requires those involved in the institutions to... Sports have garnered significant attention for guiding these strategies in all aspects and specific situations. From this perspective, the problem addressed in this study is formulated by seeking the answer to the following logical question: